Wittgenstein and Ethical Supervenience - Dabbagh, Soroush (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
In this, paper, I am going to present an argument in favour of generalism and criticise the particularistic position in moral reasoning... According to generalism which is associated with supervenience, the way in which a morlly relevant feature contributes to the moral evaluation of different contexts is patternable. However, a particularist like Dancy utilizes the very idea of resultance instead of supervenience to give an account of how a non-moral feature behaves in different contexts. An account drawn from Wittgenstein with regard to the nature of concepts is presented here to criticise the particulristic position while endorsing the very idea of supervenience and the generilistic position with regard to the extent of the patternability of the reason-giving behaviour of a morally relevant feature in different contexts.